MO327: Acute Kidney Injury in Post Liver Transplantation in a Hospital in BogotÁ, Colombia. (3rd May 2022) - Molano-Triviño, Alejandra; Martínez, Carlos; Saumett, Sandra; Conde, Rafael; Varón, Adriana; Gutiérrez Rueda, Laura; Rojas, Daniel; Galindo, Camila
Abstract: BACKGROUND AND AIMS: Liver transplantation is a mandatory treatment for many cirrhotic patients worldwide. Nonetheless, frequently there is high systemic morbidity and considerable mortality in post transplantation [1 ]. Our aim was to calculate acute kidney injury incidence (KDIGO), need of renal replacement therapy, early liver graft dysfunction (first week post transplantation: Bilirubin > 10 mg/dL, INR > 1.5, ALT or AST > 2000 UI) and calculate mortality between liver transplantation and end of evaluation. METHOD: We reviewed clinical registries from our transplantation service in La Cardio Hospital in Bogotá, Colombia, and included adult patients with diagnosis of cirrhosis and liver transplantation (Ltx) between 1 January 2005 and 31 July 2021. We excluded patients with acute liver failure without indication of transplantation, previous transplant or multiorganic transplantation (e.g. liver–kidney), heart failure and GFR < 30 mL/min/1.73 (CKD EPI). RESULTS: We had 550 Ltx patients, of whom 397 (54.4% male) were included according to our inclusion criteria. Mean age of population was 56 year old at the moment of Ltx. Medical history of comorbidity was hypertension (15.8%), diabetes (24.1%) and smoking (25.44%). Mean Charlson index was 4.4 (Ds ± 1.5). Main etiologies of cirrhosis were alcohol (17.8%), idiopathic (16%), hepatitis C virus (15.3%). In terms of cirrhosis severity, 52.3% had CHILD B, and 26% CHILD C. Average MELD-Na was 16 (Ds ± 6). Anhepatic time was 57 min (RIQ: 47–69). Mean time in ICU was 2 days. There was early graft dysfunction in 32 patients (8%). AKI was diagnosed in 21% of patients. Renal replacement therapy was initiated in 29 patients. Global mortality was 15.1% during the time of study. We performed a classification and regression tree (CART) analysis, using mortality, graft dysfunction and AKI as variables. In CART for mortality, patients with BMI < 19 had 56% of probability of death. The absence of RRT need was related to a 95% probability of being alive at the end of the follow-up. A BMI > 19 and < 24 in need of RRT was associated to a 55% of probability of death (Graphic 1 ). In terms of graft dysfunction, it was present in 8% of patients. Patients taken to RRT had 55% of probability to death. Acute kidney injury was diagnosed in 21% of patients, classified according to KDIGO: 1: 38%, 2: 32% and 3: 30%. Patients who needed RRT showed a higher prevalence of diastolic dysfunction (88%). The majority of KDIGO 3 patients did not need RRT (Graphic 2 ). CONCLUSION: Acute kidney injury was present in almost one quarter of liver transplantation patients and was related to an increase in mortality. We consider that those results highlight the importance of kidney function evaluation from the early post-operative state in a nephrology rapid response team scheme aligned with transplantation surgery, ICU and anaesthesia to improve AKI prevalence.